Design of Interactive Media on Dynamic Electricity as Alternative Physics Learning Approach - Suci Prihatiningtyas; Siti Hamidah; Novia Ayu Sekar Pertiwi; Syam Sudin (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The development of digital technology has brought significant transformations in various aspects of life, including education. This study aims to develop and validate interactive learning media based on the Canva application for the topic of Dynamic Electricity. Physics learning in secondary schools is still hampered by the dominance of conventional methods and the use of static, non-interactive media, resulting in low student engagement and weak conceptual understanding, especially in dynamic electricity materials. The media is designed to visualize abstract concepts such as current, voltage, resistance, and Ohm's Law to make them easier for students to understand. This research is a research and development study referring to the development model proposed by Borg and Gall. Validation was carried out by material experts, media experts, and linguists. The validation results indicate that the media is considered very valid and feasible for use, with eligibility criteria including content, accuracy, design, and language use. Thus, this media has the potential to increase student motivation and understanding. However, this research is still limited to the validation stage; therefore, further classroom trials are needed to measure its effectiveness.